Influence of Fly Ash Addition on Nutrient and Microbial Population in Citronella Leaf Waste Composting - Zuhriansah, Alfi Laila; Mansur, Irdika; Budi R, Sri W.; Astuti, Ria; Lubis, Rizky Febriana Br; Rahmah, Hanifa; Shrena, Mona Fitri; Kusuma, Yosie Syadza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The response of composting microbes to fly ash can show an increase or decrease in population depending on the type and concentration of fly ash used. This study aims to identify the effect of fly ash addition on the composting of citronella (Cymbopogon nardus (L.) Rendl.) leaf waste, specifically in relation to changes in the C/N ratio and the number of composting microbes, and the identification of fungal species that developed during the process. The composting treatments included citronella leaf waste without alkali (K), also with the addition of alkali in the form of 2% dolomite (D), fly ash of 2% (FA1), 5% (FA2), 10% (FA3) and 15% (FA4). The analysis used in this study was a quantitative descriptive analysis related to the analysis of C-organic and total N, as well as composting microbes. Quantitative descriptive analysis was employed to assess C-organic content, total nitrogen, and microbial populations. The results demonstrated that the incorporation of fly ash influenced both the C/N ratio and microbial abundance. The addition of 10% fly ash proved to be the most effective treatment, increasing nitrogen content and reducing the C/N ratio to 26, while supporting bacterial growth up to 3.0 × 10¹¹ CFU/g. Fungal identification revealed the presence of Rhizopus sp., Trichoderma sp., and Aspergillus sp., which contribute to the degradation of organic matter in citronella leaf waste.